2015
DOI: 10.1021/acsami.5b09346
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Electrochemical Activity of Epitaxial Mg-Spinel Thin Films

Abstract: We report an approach to control the reversible electrochemical activity (i.e., extraction/insertion) of Mg(2+) in a cathode host through the use of phase-pure epitaxially stabilized thin film structures. The epitaxially stabilized MgMn2O4 (MMO) thin films in the distinct tetragonal and cubic phases are shown to exhibit dramatically different properties (in a nonaqueous electrolyte, Mg(TFSI)2 in propylene carbonate): tetragonal MMO shows negligible activity while the cubic MMO (normally found as polymorph at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
0
56
0
Order By: Relevance
“…17,18 Their utilization for biomedical applications has increased significantly over the last years, especially in the fields of drug delivery 19 and biosensors. 20,21 In addition to their applications as magnetic materials, it is worth mentioning that SFs are widely used for other purposes, e.g., as catalysts for very varied chemical processes, 22,23 advanced battery electrodes, 24,25 electrochemical supercapacitors in energy storage systems, 26 etc.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Their utilization for biomedical applications has increased significantly over the last years, especially in the fields of drug delivery 19 and biosensors. 20,21 In addition to their applications as magnetic materials, it is worth mentioning that SFs are widely used for other purposes, e.g., as catalysts for very varied chemical processes, 22,23 advanced battery electrodes, 24,25 electrochemical supercapacitors in energy storage systems, 26 etc.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, MgMn 2 O 4 with particle sizes of 11-200 nm were synthesized by various processes such as sol-gel and co-precipitation methods, and their cathode performances were investigated. [12][13][14][15][16][17][18][19][20][21][22][23] Some reports demonstrated high specic capacities, but so far, there are no reports where high capacity could be obtained at high rates with an anhydrous electrolyte under ambient temperature. Since decreasing the particle size is one of the most effective ways to enhance the specic capacity and the rate capability for suppressing the slow Mg 2+ diffusion in solids, 24 alternative synthetic methods that enable nanoparticles below 10 nm are required for achieving a breakthrough in such cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the magnesium manganese oxide spinel MgMn 2 O 4 is different compared to the typical cubic structure of other spinels, mainly due to the Jahn‐Teller effect of Mn 3+ . It is a partially inverted spinel with a majority of Mn(III) in the octahedral sites as well as a fraction of Mn(IV) and Mn(II) in the octahedral and tetrahedral sites [162] . Despite the sluggish diffusion of Mg 2+ into the tetragonal spinel, experiments revealed that the delithiated cubic phase λ‐Mn 2 O 4 can insert Mg 2+ in aqueous and non‐aqueous electrolyte [103,162] .…”
Section: Magnesium Cathode Materialsmentioning
confidence: 99%